2017
DOI: 10.3389/fpls.2017.00037
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of RALF Proteins in Green Plants Suggests There Are Two Distinct Functional Groups

Abstract: Rapid Alkalinization Factors (RALFs) are small, cysteine-rich peptides known to be involved in various aspects of plant development and growth. Although RALF peptides have been identified within many species, a single wide-ranging phylogenetic analysis of the family across the plant kingdom has not yet been undertaken. Here, we identified RALF proteins from 51 plant species that represent a variety of land plant lineages. The inferred evolutionary history of the 795 identified RALFs suggests that the family ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
178
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(189 citation statements)
references
References 52 publications
4
178
7
Order By: Relevance
“…). According to Campell and Turner () RALF sequence classifications FaRALF33‐like belongs to the clade I subfamily of RALF peptides, since its mature form contains the YISY, YYNC and CRC motifs typical of this clade (Supplementary Fig. ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…). According to Campell and Turner () RALF sequence classifications FaRALF33‐like belongs to the clade I subfamily of RALF peptides, since its mature form contains the YISY, YYNC and CRC motifs typical of this clade (Supplementary Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…RALF peptides have been linked to several physiological and developmental processes, including cell expansion (Haruta et al , ), lateral root development (Murphy et al , ), root hair growth (Wu et al , ), pollen tube elongation (Covey et al , ), nodulation in legumes (Djordjevic et al , ) and stress (Atkinson et al , ). In silico analysis of the Arabidopsis thaliana genome identified 37 genes belonging to the RALF family, named RALF1 to RALF37 (Olsen et al , ), and the homologues identified in other species have been named according to their similarities to the members of the A. thaliana family (Campbell and Turner, ). The RALF pleiotropic role indicates that these peptides are key players in plant development.…”
Section: Introductionmentioning
confidence: 99%
“…Hierarchical clustering has grouped the CLE genes into four groups (I-IV), labeled on the right. 2017), and RALF (Campbell and Turner, 2017) families. However, the extensive, manual curation performed in this study ensured high confidence in all known SSP families and the corresponding HMMs, which will enable high-quality annotation of a broad range of SSP families in other plant species.…”
Section: Genome Reannotation and The Comprehensive Identification Of mentioning
confidence: 96%
“…). Subsequently more than 30 RALF and RALF‐related genes were identified in Arabidopsis and their function is only beginning to emerge (Murphy & De Smet ; Campbell & Turner ). In contrast to the previously discussed small post‐translationally modified peptides, RALFs are not perceived by LRR‐RLKs, but rather by malectin‐like‐domain‐containing receptor kinases of the Catharanthus roseus RLK1‐like (CrRLK1L) family.…”
Section: Post‐translationally Modified Peptides and Peptide Familiesmentioning
confidence: 97%
“…; Srivastava et al . ; Campbell & Turner ), which is quite misleading. Yes, the motif does contain two basic amino acids and these residues are in fact required for substrate recognition (Matos et al .…”
Section: Different Types Of Ptm and Their Relevance For Peptide Biogementioning
confidence: 99%